Ethnomedicinal Uses of Plant Species in Panchase Protected Forests (A Case Study including the Kaski, Parbat & Syangja Districts of Nepal) - Neupane, Asmit; Dhakal, Anisha; Lamsal, Urusha; Sharma, Barsha; Thapa, Roshna (International Journal of Applied Biology, 2024)
Ethnomedicinal plants, which have been utilized by indigenous communities in Nepal for centuries, hold promise for treating various ailments. Globally, medicinal plants are integral to healthcare systems, with Nepal renowned for its rich biodiversity and indigenous knowledge. This manuscript explores the ethno-medicinal practices within Nepal's Panchase protected forest, aiming to validate traditional remedies and contribute to healthcare improvement. Through a comprehensive study involving reconnaissance surveys, interviews, and data analysis, 103 ethno-medicinal plants from 58 families were documented, with Asteraceae being dominant. Various plant parts were utilized for treating 57 ailments, with leaves being most common. Gastrointestinal issues were prevalent, with plants such as Gheu kumari and Harro being frequently employed. Additionally, plants such as Dhursul and Ghodtapre were used for fever and migraine, while Khole Saag and Pani Amala addressed blood pressure and diabetes concerns. This study focuses on the importance of traditional medicine in rural healthcare and underscores the need for its preservation. Conservation efforts and intergenerational knowledge transfer initiatives are vital to safeguarding indigenous wisdom. Phytochemical and pharmacological studies are recommended to validate traditional knowledge scientifically. The commercial cultivation of medicinal plants could alleviate pressure on natural habitats and promote sustainable healthcare practices. This research contributes to the documentation of valuable ethno-medicinal knowledge, emphasizing its potential for socioeconomic development and healthcare enhancement in Nepal's rural communities.